2020
DOI: 10.1093/bib/bbaa230
|View full text |Cite
|
Sign up to set email alerts
|

Robust Huber-LASSO for improved prediction of protein, metabolite and gene expression levels relying on individual genotype data

Abstract: Least absolute shrinkage and selection operator (LASSO) regression is often applied to select the most promising set of single nucleotide polymorphisms (SNPs) associated with a molecular phenotype of interest. While the penalization parameter λ restricts the number of selected SNPs and the potential model overfitting, the least-squares loss function of standard LASSO regression translates into a strong dependence of statistical results on a small number of individuals with phenotypes or genotypes divergent fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…The expression of PYGL was predicted based on seven SNPs, which should suffice to accurately predict gene expression. The negative correlation between measured and predicted expression of PYGL (ρ = −0.58) in our study is unlikely the result of an insufficient number of eQTLs as previous studies reported that genetically regulated gene expression seems to be associated with a small number of variants rather than with multiple eQTLs [27,28]. Nevertheless, the expression of better predicted gene TRIM4 (ρ = 0.19) was based on 26 genetic variants.…”
Section: Discussioncontrasting
confidence: 48%
“…The expression of PYGL was predicted based on seven SNPs, which should suffice to accurately predict gene expression. The negative correlation between measured and predicted expression of PYGL (ρ = −0.58) in our study is unlikely the result of an insufficient number of eQTLs as previous studies reported that genetically regulated gene expression seems to be associated with a small number of variants rather than with multiple eQTLs [27,28]. Nevertheless, the expression of better predicted gene TRIM4 (ρ = 0.19) was based on 26 genetic variants.…”
Section: Discussioncontrasting
confidence: 48%
“…LASSO Cox regression is a cutting-edge approach to quantify the impact of various features in the selection process. In particular, a 10-fold cross-validation technique was utilized to ensure the most robust results and to ascertain the optimal value of lambda (λ), which is the key component of the feature selection procedure [16,17]. In LASSO Cox regression, the coe cients of some variables are compressed to zero as λ increases.…”
Section: Nomogram Development and Risk Strati Cationmentioning
confidence: 99%
“…These characteristics of LASSO befit the gene expression data as a feature selection model. LASSO has elucidated excellent performance in numerous studies [55][56][57][58] , delineating as a very promising feature selection model. The variables with relative scaled importance >10 was considered significantly important.…”
Section: Regularized Regression Modelsmentioning
confidence: 99%